Quality-Based Educational Facilities and Infrastructure Management Model for Learning Improvement at MI Mambaul Ulum Tlogorejo Karangawen Demak - Muhamad Mundir; Joko Widodo; Sari Hernawati (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Improving learning quality requires educational facilities and infrastructure to be managed through systematic and quality-oriented approaches rather than conventional administrative practices. This study aimed to examine the implementation of educational facilities and infrastructure management at MI Mambaul Ulum Tlogorejo Karangawen Demak, identify the factors influencing its effectiveness, and develop a context-specific Quality-Based Educational Facilities and Infrastructure Management Model. A qualitative single-case study was conducted over a three-month period using purposive sampling involving 16 participants, comprising one principal, one vice principal for facilities and infrastructure, six teachers, two administrative staff members, two school committee representatives, and four parents. Data were collected through semi-structured interviews, non-participant observations, and document analysis and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the effectiveness of educational facilities management was evidenced by more systematic facilities utilization, improved learning quality, enhanced teacher performance, and greater student engagement, which were achieved through strategic planning, transparent resource allocation, stakeholder collaboration, preventive maintenance, continuous monitoring, evidence-based evaluation, and sustained quality assurance. Based on these empirical findings, this study proposes a context-specific conceptual Input–Process–Output–Feedback (IPOF) management model comprising four interconnected components: Input (vision, regulations, human resources, budget, and stakeholders), Process (planning, procurement, utilization, maintenance, monitoring, and evaluation), Output (effective facilities, improved learning quality, teacher performance, and student engagement), and Feedback (continuous improvement, strategic review, and quality assurance). This model extends the application of Total Quality Management principles into an integrated educational facilities management framework that may guide quality improvement in Islamic primary schools and similar educational contexts.